Socioeconomic and demographic factors associated with abdominal obesity in women of childbearing age - Amira Kurspahić-Mujčić; Emir Zećo (Medicinski glasnik, 2017)
Aim: To determine socioeconomic and demographic factors associated with abdominal obesity in women of childbearing age. Methods: This cross-sectional study was carried out in family medicine outpatient departments of the Primary Health Care Centre of Canton Sarajevo, Bosnia and Herzegovina. The study included 300 respondents who were divided into two groups: non-abdominal obesity (n=150) and abdominal obesity (n=150). Abdominal obesity was estimated measuring waist circumference. Data concerning socioeconomic and demographic factors (age, marital status, "live alone", place of residence, formal education level, self-perceived financial status) were collected using a designed questionnaire. Logistic regression analysis was used to estimate the association between socioeconomic, demographic factors and abdominal obesity. Results: Abdominal obesity was significantly associated with the life in the urban area (OR=2.174, 95%CI=1.362-3.471), university education (OR=9.881, 95%CI=3.222-30.301) and slightly better financial status than average (OR=2.412, 95%CI=1.302-4.470). Marital status (OR=0.190, 95%CI=0.104-0.347) and no living alone (OR=0.357, 95%CI=0.165-0.773) protect from abdominal obesity. Respondents aged between 20-29 years represent a particularly vulnerable group in terms of abdominal obesity (OR=1.030, 95%CI=0.097-10.946). Conclusion: The strongest associations have been found between abdominal obesity and education. Public health programs that aim to reduce abdominal obesity in women of childbearing age should mainly focus on women with university education.
Keywords: abdomen; adipose tissue; female; social-class